2023
DOI: 10.18502/kss.v8i1.12635
|View full text |Cite
|
Sign up to set email alerts
|

Exploring How the Covid-19 Pandemic has Changed Greek Consumers' Habits

Abstract: The recent COVID-19 pandemic has impacted various aspects of consumer behavior and affected spending levels. In addition, businesses have had to adapt to everchanging environmental conditions to survive this global health, economic, and social crisis. The online market has taken an important place in people’s daily lives, while e-commerce sales and social media usage increased during this period. The main objective of this article was to examine how the COVID-19 pandemic affected and changed consumer behavior.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“… Bareja-Wawryszuk et al (2022) found that there were clear differences in the nature of changes in consumer behavior between respondents from Turkey and Poland, with the purchasing habits of respondents in Turkey changing to a greater extent. Argyropoulou et al (2023) found that the pandemic has impacted various aspects of consumer behavior in Greece, with online shopping and social media usage increasing during this period. The papers suggest that the COVID-19 pandemic has had a significant impact on online shopping behavior.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“… Bareja-Wawryszuk et al (2022) found that there were clear differences in the nature of changes in consumer behavior between respondents from Turkey and Poland, with the purchasing habits of respondents in Turkey changing to a greater extent. Argyropoulou et al (2023) found that the pandemic has impacted various aspects of consumer behavior in Greece, with online shopping and social media usage increasing during this period. The papers suggest that the COVID-19 pandemic has had a significant impact on online shopping behavior.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…The COVID-19 pandemic has significantly influenced consumer behavior, resulting in notable transitions in E-commerce sales and heightened engagement with social media platforms (Argyropoulou et al, 2023). As a prominent platform within the digital view, social media presents significant avenues for influencing human behaviors and concurrently facilitating the observation of resultant effects.…”
mentioning
confidence: 99%